Conceptualizing and Measuring Collaboration - Thomson, A. M.; Perry, J. L.; Miller, T. K. (Journal of Public Administration Research and Theory, 2007)
This article conceptualizes and measures collaboration. An empirically validated theory of collaboration, one that can inform both theory and practice, demands a systematic approach to understanding the meaning and measurement of collaboration. We present ﬁndings from a study that develops and tests the construct validity of a multidimensional model of collaboration. Data collected using a mail questionnaire sent to 1382 directors of organizations that participate in a large national service program provides the basis for a higher order conﬁrmatory factor analysis. The model that emerges from this analysis demonstrates an overall close ﬁt with the empirical data and the high, standardized gamma coefﬁcients estimated in the model conﬁrm that ﬁve key dimensions contribute to an overall construct of collaboration. The primary purpose of this research was to stimulate interest in measurement of collaboration and reﬁnement of the model. As such, we present a detailed description of the analytical process, identify areas that affect interpretation of the data (such as possible selection bias), and propose areas for future research. We believe this effort to conceptualize and measure collaboration offers a foundation for further research.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; collaboration / colaboração

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Publisher: SAGE Publications Ltd
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Number: 1 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1748-3131.2007.00058.x
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico